The Principal’s Strategy in Improving the Quality of Education Through Management of Infrastructure at MTs Al-I’anah Kosambi Karawang - Awaliyah, Luthfi; Kosim, Abdul; Kasja, Kasja (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to find problems in improving the quality of education by fulfilling the existing infrastructure in schools. This study uses a qualitative method. Data were collected by direct observation to the field. The results of the study show that problems in improving the quality of education are found in the fulfillment of inadequate infrastructure facilities, as for the strategies carried out by school principals in improving the quality of education through the management of infrastructure, namely, inviting parents of students to come to school which aims to carry out socialization regarding the problem of the lack of existing infrastructure in schools in order to improve the quality of education, the next strategy the principal is to partner with industry or companies to design infrastructure needs that must be met by working together in improving the quality of education at MTs Al-i’anah Kosambi Karawang.